Cross-Cultural Validation of the RECAP of Atopic Eczema Questionnaire in a Swedish Population - Gunnthorunn Sigurdardottir; Mikael Alsterholm; Chris D. Andersson; Maria Bradley; MariHelen Sandström Falk; Emma K. Johansson; Maria Lundqvist; Andreas Sonesson; Åke Svensson; Grigorios Theodosiou; Sophie Vrang; Laura B. von Kobyletzki (Medical Journals Sweden, 2024)
A Swedish translation of the patient-reported outcome measure for assessing long-term control of atopic dermatitis, Recap of atopic eczema (RECAP), has not been validated. Cross-cultural translation and multi-centre validation of the translated RECAP questionnaire were therefore performed. Disease severity was assessed using the validated Investigator Global Assessment Scale for atopic dermatitis (vIGA-ADTM). The Swedish RECAP was completed by 208 individuals aged 16 years or older with a median age of 36 years (interquartile range [IQR] 27-48). The participants considered the questionnaire suitable for assessing eczema control. The median RECAP score (range 0-28) was 12 (IQR 5-19). The mean and median vIGA-ADTM scores (range 0-4) were 2 (standard deviation [SD] 2) and 3 (IQR 2-4), respectively. A correlation between RECAP and the vIGA-ADTM was observed (p < 0.001). There was no significant change in scores for participants who answered the questionnaire twice within 14 days. Over time, improved or worsened eczema, as evaluat-ed by vIGA-ADTM, affected RECAP scores significantly (p < 0.001). The study suggests that RECAP can assess AD control in a Swedish clinical setting and shows -acceptable reliability.